The demographic changes in the accident insurance systems and its impact on competitivity : the Barbados experience - Nunez, Richard (ISSA [Geneva]CH, 2008)
Analyzes the claims experience of the Barbados system of accident insurance in order to examine the extent to which accident rates are related to age and gender.